Effects of mrpigG on Development and Secondary Metabolism of Monascus ruber M7 - Li Li; Fusheng Chen (Journal of Fungi, 2020)
Monascus pigments (MPs) have been used as food colorants for several centuries in Asian countries and are now used throughout the world via Asian catering. The MP biosynthetic pathway has been well-illustrated, but the functions of a few genes, including mrpigG, in the MP gene cluster are still unclear. In the current study, in order to investigate the function of mrpigG in M. ruber M7, gene deletion (ΔmrpigG), complementation (ΔmrpigG::mrpigG) and overexpression (M7::PtrpC-mrpigG) mutants were successfully obtained. The morphologies and biomasses, as well as the MP and citrinin production, of these mutants were analyzed. The results revealed that the disruption, complementation and overexpression of mrpigG showed no apparent defects in morphology, biomass or citrinin production (except MP production) in ΔmrpigG compared with M. ruber M7. Although the MP profiles of ΔmrpigG and M. ruber M7 were almost the same—with both having four yellow pigments, two orange pigments (OPs) and two red pigments (RPs)—their yields were decreased in ΔmrpigG to a certain extent. Particularly, the content of rubropunctatin (an OP) and its derivative rubropunctamine (an RP) in ΔmrpigG, both of which have a five-carbon side chain, accounted for 57.7%, and 22.3% of those in M. ruber M7. On the other hand, monascorubrin (an OP) and its derivative monascorubramine (an RP), both of which have a seven-carbon side chain, were increased by 1.15 and 2.55 times, respectively, in ΔmrpigG compared with M. ruber M7. These results suggest that the MrPigG protein may preferentially catalyze the biosynthesis of MPs with a five-carbon side chain.